2018
DOI: 10.1515/helia-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Crop Yield and the Quality of Sunflower Seeds in the Use of Fertilizers and Growth Regulation Substances

Abstract: In the Russian Federation the most favorable area for high and stable yields of sunflower crop is the Northern zone of Krasnodar region. The research was conducted in multivariate experience of long-term stationary monitoring. We researched the effect of doses of mineral fertilizers and furolan on sunflower yield and seed quality. It was found that it is expedient and cost-effective to use small doses of nitrogen fertilizers for sunflower. The expediency of application of plant growth regulator (Furolan) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…Theoretical studies and practical experience have shown that high yields per unit area are usually associated with the number of plants per unit area, number of seeds per plant (depending on the degree of fertilization), head diameter (Hladni et al, 2014;Singh & Chander, 2018;Zeinalzadeh-Tabrizi et al, 2019;Riaz et al, 2019;Keipp et al, 2020;Naik & Ghodke, 2021) and the weight of 1000 seeds (Radić et al, 2013;Jalil et al 2014;Nichal et. al., 2015;Ieremenko & Kalitka, 2016;Kvashin et al, 2018;Baraiya et al, 2018;Kalenska et al, 2020;Radić et al, 2021;Naik & Ghodke, 2021). The authors mentioned above also argue that increases in the weight of 1000 seeds and head diameter significantly increase seed yields, which is consistent with the results obtained herein.…”
Section: ____________________________________________________________...supporting
confidence: 86%
See 1 more Smart Citation
“…Theoretical studies and practical experience have shown that high yields per unit area are usually associated with the number of plants per unit area, number of seeds per plant (depending on the degree of fertilization), head diameter (Hladni et al, 2014;Singh & Chander, 2018;Zeinalzadeh-Tabrizi et al, 2019;Riaz et al, 2019;Keipp et al, 2020;Naik & Ghodke, 2021) and the weight of 1000 seeds (Radić et al, 2013;Jalil et al 2014;Nichal et. al., 2015;Ieremenko & Kalitka, 2016;Kvashin et al, 2018;Baraiya et al, 2018;Kalenska et al, 2020;Radić et al, 2021;Naik & Ghodke, 2021). The authors mentioned above also argue that increases in the weight of 1000 seeds and head diameter significantly increase seed yields, which is consistent with the results obtained herein.…”
Section: ____________________________________________________________...supporting
confidence: 86%
“…Hladni et al (2014) argues that there is a significantly high degree of variability in seed yields between inbred sunflower lines. The external environment has a great influence on the variability in sunflower seed yields (Radić et al, 2020), as well as the genotype itself (Kvashin et al, 2018). In addition to genetic factors (the genotype), sunflower seed yields are also conditioned by cultural practices applied and environmental conditions.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…However, other factors (SD and the interaction between SD and G) also exhibited a statistically significant effect, as confirmed by Krstić et al [42]. Environmental conditions, genotype, and applied agronomic practices have a substantial impact on seed and oil yield variation, as reported by Ion et al [43], Kvashin et al [44], and Radić et al [45]. Furthermore, different factors exhibited varying effects on Y and OY during different years of the study.…”
Section: Factor Share In the Variation Of All Examined Traitssupporting
confidence: 69%